Development and Validation of Adherence Score for Subcutaneous Biologic Disease-Modifying Antirheumatic Drugs - Abdul Razak, Salmi; Makmor Bakry, Mohd; Mohamed Said, Mohd Shahrir; Tan, Chai-Eng; Md Redzuan, Adyani (Frontiers in Pharmacology, 2020)
Background: The biologic disease-modifying antirheumatic drugs (bDMARDs) are currently incorporated as part of the pharmacotherapy management of inflammatory arthritis (IA). Adherence to bDMARDs is crucial to ensure treatment success in IA. However, most of the recent studies evaluated adherence level in patients using subcutaneous injections of bDMARDs utilized the indirect methods adapted from adherence assessment for oral medication. Aim: This study aimed to develop a questionnaire to assess adherence to the self-injectable subcutaneous bDMARDs. Methods: The development of the Subcutaneous bDMARDs Adherence Score (SCADS), involved evaluation of Content Validity. Literature reviews provide the basis for domain identification and items formation. Four experts evaluated the instrument by using a 4-point ordinal scale with a rubric scoring on relevance, importance, and clarity of each item in measuring the overarching construct. The Item Level Content Validity Index (I-CVI), and the scale-level content validity index (S-CVI) were calculated. The factor structure and internal consistency reliability of SCADS were estimated using principal component analysis (PCA) and Cronbach’s alpha, respectively. Results: Both S-CVI/UA (Universal Agreement) and the averages item-level content validity index (S-CVI/Ave) (Average) for the entire instrument showed excellent criteria with a value of >0.90. The Cronbach’s alpha coefficient value for SCADS was 0.707 indicating good internal consistency. All items showed corrected item-total correlation coefficients above 0.244. Questionnaire items with a factor loading of 0.30 or above were considered in the final factor solution. The factor analysis resulted in 3-factor solutions, which corresponded to 66.62% of the total variance. Conclusion: The SCADS is a consistent and reliable instrument for evaluating adherence among IA patients using the subcutaneous bDMARDs . It is simple to use yet comprehensive but still requiring further clinical and international validation.